Restricted Donations to a Parish: Canon 1267 - Renken, John A. (Roman replies and CLSA advisory opinions ; 2012, 2012)
Our parish church, school, and rectory are in need of signifi,cant repairs. A well-intended parishioner recently told our pastor that, from now on, she will only give donations for "special purposes" to the parish (e.g., for the repair of the church roof). She believes that giving such "restricted donations" will assure that they remain with the parish. She wants nothing of her donations to reach the diocese or to be subject to the annual diocesan tax. Can the pastor accept such gifts? If so, must they be reported as "ordinary parish income"? And would they be subject to the diocesan tax, or not?